The Analysis of Company Size, Complexity of Operation, Profitability, Solvency and Audit Firm Size toward Timeliness of Financial Statement Reporting for Company listed in LQ45 Index in Indonesia Stock Exchange (2012 – 2014) - Raditya Pratama; Monika Kussetya Ciptani (President University Press, 2018)
Companies are required to submit their annual report timely after the end of fiscal year to support stakeholder’s need of information. Financial statements would have benefits if delivered accurately and timely to the users for decision making. This research is aimed to identify the effect of company size, complexity of operation, profitability, solvency, and audit firm size toward the timeliness of financial statements reporting in companies that are listed in LQ45 index from 2012 to 2014 either simultaneously and partially. The research involves 69 samples, which consist of 3 years data of 23 companies that are consistently listed in LQ45 index from 2012 to 2014. The research found that complexity of operation, profitability, and audit firm size are statistically significant toward the timeliness of financial statements reporting. While company size and profitability are not statistically significant toward the timeliness of financial statements reporting. The F-test result revealed that one or more independent variables have significant influence toward the timeliness of financial statements reporting. Then, the R2 analysis showed that the regression model is able to describe timeliness of financial statements reporting by 26.3%. The rest 73.7% is explained by other factors apart from this research.